La paradoja arbitral: cuestiones de límites y "cultura de las pretensiones territoriales" en Hispanoamérica - Domínguez Benito, Héctor (Jahrbuch für Geschichte Lateinamerikas, 2023)
This article analyzes the problems connected with the submission to arbitration of boundary disputes between Hispanic American states at the turn of the twentieth century. While the institutionalization of arbitration was a goal widely promoted by international legal scholars and diplomats from Spanish America, several actors involved in the dispute or resolution of such controversies at the time hesitated on its appropriateness. Doubts were raised over the possibility of submitting to the judgment of a third party matters that could eventually affect the territorial integrity or sovereignty of the republics, as well as other abstract concepts characteristic of the time such as national honor and dignity. Such skepticism is closely connected to another important element of the period: the progressive sacralization and increasing popularity in nationalist discourses of the alleged demarcations of the Spanish Monarchy.
Keywords: Borders; International Law; Diplomacy; Nationalism; Uti Possidetis Iuris